Landscape with figures : nature and culture in New England - Ryden, Kent C., 1959- (American land and life series., 2001)
Traveling across the invisible landscape in which we imaginatively dwell, Kent Ryden--himself a most careful listener and reader--asks the following questions. What categories of meaning do we read into our surroundings? What forms of expression serve as the most reliable maps to understanding those meanings?